The Effect Of Incentives On Employee Performance Through Career Development As A Variable Intervening In The Employment Service General And Spatial Planning Asahan Regency - Ira Junianty; Muhammad Isa Indrawan (International Journal of Management, Economic and Accounting, 2025)
Providing the right incentives and structured career development programs are important factors in improving employee performance in government organizations. This study aims to find out and analyze the influence of incentives on employee performance mediated by career development at the Asahan Regency Public Works and Spatial Planning Office. This study uses a causal associative quantitative approach. The sample used was the entire employee population of 145 people with a saturated sampling technique. Data analysis was carried out using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The results showed that incentives did not have a significant direct influence on employee performance, with a T-statistical value of 1.516 < 1.96 and a P-value of 0.132 > 0.05. However, incentives had a positive and significant effect on career development, with a T-value of 55,921 > 1.96 and a P-value of 0.000 < 0.05, indicating that incentives encourage employee involvement in career development programs. Career development also had a positive and significant effect on employee performance, with a T-statistical value of 8.826 > 1.96 and a P-value of 0.000 < 0.05, indicating that career development is able to improve employee performance. In addition, career development mediates the influence of incentives on employee performance, shown by a T-statistical value of 8.389 > 1.96 and a P-value of 0.000 < 0.05. These results provide insight that structured career development can strengthen the incentive effect in improving employee performance at the Asahan Regency Public Works and Spatial Planning Office.